Blood foam : a Lewis Cole mystery - DuBois, Brendan (DuBois, Brendan. Lewis Cole mystery., 2015)
Lewis Cole-retired Department of Defense analyst and magazine columnist-returns to his fire-damaged home on Tyler Beach with two things on his mind: to recover from a bullet wound and to repair his nearly two hundred-year-old home before a hurricane scours his house. But just when his work has begun, former lover and journalist Paula Quinn comes to him with an urgent request. Her fiancé, attorney Mark Spencer, has gone missing. Lewis Cole is Paula's last hope to find her missing fiancé, but one puzzling aspect of Mark's life leads to Lewis asking more questions... until gunfire suddenly erupts in placid downtown Tyler. And Lewis and Paula find themselves on the run from a deadly gang, who are also searching for Mark Spencer-to find him and kill him for a past betrayal. So Lewis begins a difficult quest while his own world is threatened by ruthless men and gathering storm clouds.